Postclassicism, disturbed philology and Kleist's Fencing Bear - Guthenke, C (Routledge, 2018)
This article reads Kleist’s narrative dialogue essay ‘Über das Marionettentheater’ (1810) as a text that is instructive for scholars examining the culture of classical education and the disciplines of knowing, interpreting and reading around 1800. This means mobilizing Kleist as a disruptive guide to emblematic tropes of disciplinary enquiry and pedagogy, especially those glossed on the Platonic desire for knowledge. What Földényi called a drama of ‘disturbed erotics’ is thus also a drama of ‘disturbed philology’. It is, at the same time, a reminder that the structures of artistic and literary classicism around 1800 are closely bound up with the structures of classical knowledge and its increasingly professionalized practices, especially in light of their emphasis on teaching, understanding and ‘Bildung’.